Trade and Competition Policies in Imperfectly Competitive Markets - Domenico Buccella (FIW - Research Centre International Economics, 2008)
This work analyzes the difference between trade policy and competition policy for prices, wages, employment and national welfare when both product and labor markets are imperfectly competitive. Trade and competition policies have different impact on the domestic labor market when it is unionized. While competitive policies increase union welfare, imports from a foreign country reduce it. Competition policy in the presence of national labor unions does not reduce labor market distortions, while competition induced by trade policy from a foreign exporter reduces both labor and product market distortions and competition is harsher as long as a foreign union is more employment oriented. The impact of both policies on the domestic welfare level is analyzed.
Keywords: F13; J51; L12; L52; 330; Trade and competition policies; monopoly; labor unions